Influence of Microfinance Banks on Socio-Economic Status of Women in Southwestern Nigeria (2015)
MicroFinance Banks (MFBs) were established as an intervention to serve vulnerable groups, such as women, who were not served by commercial banks in Nigeria. With the array of these banks in the country, there is an expectation of a corresponding impact on women‘s socio-economic activities in the informal sector, just as it is in Bangladesh, Cambodia and Sri-Lanka. However, contrary to these expectations, the impact of MFBs on women‘s socio-economic status is scantily documented and under-represented on the human capital development and poverty indices. This study, therefore, examined the influence of MFBs on socio-economic status (communal relations, level of assertiveness, social skills, membership of societies, residence quality and health status, ownership of household assets, entrepreneurship/income generation skills and home/property ownership) of women in Southwestern Nigeria. The study adopted the descriptive survey design of the ex post facto type. Four highly acclaimed performing MFBs were purposively selected from each of Oyo, Ondo and Lagos states. The proportionate and simple random sampling techniques were used to select 1500 women clients of the 12 MFBs. Women Socio-Economic (r=0.87) and Microfinance Inventory (r= 0.82) scales were used for data collection. These were complemented with six Key Informant Interviews (KII) with microfinance officials and Focus Group Discussions (FGDs) with women clients. Five research questions were answered and three hypotheses tested at p=0.05. Data were analysed using descriptive statistics, Pearson product moment correlation, multiple regression and content analyses. Age of respondents was 45 ± 2; the microfinance-women clients‘ relationship was more of individual (90.0%) than groups (10.0%), while usage was more of business (91.0%) than general (9.0%) purposes. Microfinance services were introduced to women clients through MFBs‘ marketing (31.0%), neighbours/friends (39.0%) and relatives (30.0%). Microfinance banks‘ impact on socio-economic status (SES) of women (F(8,1291)=37.49, R= .43) accounted for 18.9% in the variance of women‘s SES. Microfinance had relative significant relationships with residence quality (r=.60), income generational skills (r= .57), health status (r=.25), members of societies (r=-.38), community relations (r=-.23) and home/property ownership (r=.22); but low relationships with level of assertiveness (r=-.08), ownership of household assets (r=.08) and social skills (r=.07). The KII report revealed that the inability of microfinance to adequately meet the working capital needs of the women clients arose from their low access to the Micro Small and Medium Enterprises Development (MSMED) funds due to the stringent requirements and regulations. The FGD results showed that the MFBs have made them to be self-employed. Microfinance banks impacted positively on socio-economic status of women with a strong influence on their residence quality and income generation skills. The banks should intensify publicity to create more awareness of their operations. Besides, flexible requirements and conditions should be attached to the accessibility of the Micro Small and Medium Enterprises Development funds, so that banks meet the needs of women clients.For MFBs to build volume, a legislation on the Micro-Small and Medium Enterprises Develpment (MSMED) Funds should be enacted or the fund be backed up by law as MFBs cannot assess it because of some stringent requirements and regulations.